An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G.; Pignatti, S.; Testi, a (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract The vegetation of the study site near Rome (Castelporziano Estate), where different woodland types occur, was analysed on the basis of ecological indicator values (Zeigerwerte) for light, temperature, continentality of climate, soil moisture, soil pH and nitrogen. Indicator values were estimated with Hill's reprediction algorithm for the flora of Central-Southern Italy relying on a database of 4,207 original relevés representing a balanced survey of the vegetation of this and surrounding areas. It was possible to obtain indicator values for an important fraction of the Italian Mediterranean flora. Results are ecologically reasonable, and it was possible to find strong correlation between the recalculated values and a few environmental variables. These correlations were not significant in an analogous test with subjectively derived scores of Ellenberg indicator values.
From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: correlation; Italy; reprediction algorithm; vegetation ecology

Vegetation of tuscan ultramafic soils in relation to edaphic and physical factors - Chiarucci, Alessandro; Robinson, Brett H.; Bonini, Ilaria; Petit, Daniel; Brooks, Robert R.; Dominicis, Vincenzo (Folia Geobotanica, 1998)
Vegetation and soil sampling were carried out in 80 plots located in five different ultramafic (serpentine) sites of Tuscany, central Italy. The physical and chemical features of each plot. were determined and the species composition and cover recorded. The exchangeable fraction of soil metals was analysed because it gives a measure of their concentrations available to plants. The plots were classified by cluster analysis and ANOVA was used to compare the environmental variables of the groups of plots. Canonical correspondence analysis was used to detect the principal factors for gradients of species composition within the plant communities. A higher content of exchangeable metals was found under the more evolved and structured plant communities, suggesting that serpentine vegetation of Tuscany is not strongly limited by soil metals, such as chromium, cobalt, nickel and magnesium, typically associated with ultramafic soils. The low nutrient content of the soils and drought stress mainly due to topographical features, appear to have a more significant role in determining the typical scattered vegetation of the Tuscan ultramafics.
Keywords: canonical correspondence analysis; Drought; serpentine; soil features; species diversity; vegetation ecology